Grayanane diterpenoid glucosides as potent analgesics from Pieris japonica. (March 2020) - Zheng, Guijuan; Jin, Pengfei; Huang, Lang; Sun, Na; Zhang, Hanqi; Zhang, Hao; Yue, Mingbo; Meng, Lingkui; Yao, Guangmin
Abstract: A total of fifteen grayanane diterpenoid glucosides including eight undescribed ones, pierisjaponosides A−H, were isolated from the leaves of Pieris japonica (Thunb.) D. Don ex G. Don (Ericaceae). Their structures were established by extensive spectros copic techniques including HRESIMS and NMR, as well as chemical methods. The absolute configurations of pierisjaponosides A, B, and D were finally established by single-crystal X-ray diffraction with Cu K α radiation. This is the first time to report the crystal structure of a 5, 9-epoxygrayanane diterpenoid glucoside. Pierisjaponoside E represents the first example of a 9 β -hydroxygrayan-1(10)-ene diterpenoid. All the isolated grayanane diterpenoid glucosides were evaluated for their analgesic activities in the acetic acid-induced writhing models in mice, and showed significant analgesic effects. Pierisjaponosides A and C–H, micranthanoside A, pieroside A, and craiobiosides A and B displayed significant analgesic effects with the writhe inhibition rates over 50% at a dose of 5.0 mg/kg. Pierisjaponoside E exhibited significant analgesic activities with the percentage inhibitions of 81.7%, 70.4%, and 52.1% at the doses of 5.0, 1.0, and 0.2 mg/kg, respectively. The preliminary structure-activity relationships of grayanane diterpenoid glucosides as potent analgesics were discussed, giving some clues to design novel analgesics. Graphical abstract: Fifteen grayanane diterpenoid glucosides including eight undescribed ones were isolated from P . japonica . The absolute configuration of pierisjaponosides A, B, and D were unambiguously established by single-crystal X-ray diffraction. All the isolated grayanane diterpenoid glucosides displayed significant analgesic effects. Image 1 Highlights: Fifteen grayanane diterpenoid glucosides including eight undescribed ones were isolated. Their absolute configurations were established by single-crystal X-ray diffraction. Pierisjaponoside E represents the first example of a 9 β -hydroxygrayan-1(10)-ene diterpenoid. Fifteen grayanane diterpenoid glucosides showed significant analgesic activities. Their structure−activity relationships were discussed.